The Role of Teachers in Instilling The Value of Hindu Ethical Philosophy - Sri Rahayu Puspawati; Komang Ayu Tri Ratna Dewi; Ida Bagus Alit Arta Wiguna (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2023)
Ethics is a very noble attitude that needs to be studied and applied by all human beings regardless of their religion. This study aims to obtain and examine the role of teachers in instilling the value of Hindu Ethical Philosophy. By using descriptive qualitative research methods. Taking location in class XI SMAN 7 Denpasar. With data collection techniques Observation, Interview and Documentation. At SMAN 7 Denpasar in instilling the value of Hindu Ethical Philosophy by 1) the task of Hinduism teachers as planners, namely before carrying out the learning process the teacher makes lesson plans, 2) the task of Hinduism teachers as implementers, namely the role of Hinduism teachers as educators teachers have an important role in providing encouragement, supervision, The role of Hinduism teachers as educators teachers have an important role in encouraging, supervising, coaching and disciplining children so that students become obedient to school rules and norms of life in family and community life, the role of Hinduism teachers as teachers must keep abreast of technological developments, so that what is conveyed to students is the latest things and not outdated, the role of Hinduism teachers as motivators in instilling religious character in students, Hindu religion teachers teach students to always have confidence and enthusiasm to get good grades and always provide encouragement to always study hard so that they can get good grades on every test held by the teacher, the role of Hindu religion teachers as mentors and trainers is expected, because students will know which one is wrong and which one is right, with guidance it is hoped that children's thinking skills will develop and gradually students will be able to have a good mindset based on their own thinking, The role of Hinduism teachers as facilitators in the form of providing facilities and infrastructure when carrying out Yoga practices to support teaching and learning activities carried out to improve students' skills in the field of self-control, and the role of Hinduism 48teachers as directors must be able to listen to students in solving the problems faced, directing students in making a decision and finding their identity. 3) the task of Hinduism teachers as assessors, namely after providing the material taught, the teacher will evaluate the material that has been taught to determine the extent of students' understanding of the material that has been taught.